2020
DOI: 10.3390/nano10102069
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Level Analog Resistive Switching Characteristics in Tri-Layer HfO2/Al2O3/HfO2 Based Memristor on ITO Electrode

Abstract: Atomic layer deposited (ALD) HfO2/Al2O3/HfO2 tri-layer resistive random access memory (RRAM) structure has been studied with a transparent indium tin oxide (ITO) transparent electrode. Highly stable and reliable multilevel conductance can be controlled by the set current compliance and reset stop voltage in bipolar resistive switching. Improved gradual resistive switching was achieved because of the interdiffusion in the HfO2/Al2O3 interface where tri-valent Al incorporates with HfO2 and produces HfAlO. The un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 52 publications
0
28
0
3
Order By: Relevance
“…Bi‐layer and tri‐layer devices have been reported recently to realize synaptic functions including long term potentiation/depression (LTP/D) and spiking timing‐dependent plasticity (STDP), but the design of functional layer still has the challenges of stability and conductance modulation linearity, which directly decide the essential synaptic functions. [ 22–24 ]…”
Section: Introductionmentioning
confidence: 99%
“…Bi‐layer and tri‐layer devices have been reported recently to realize synaptic functions including long term potentiation/depression (LTP/D) and spiking timing‐dependent plasticity (STDP), but the design of functional layer still has the challenges of stability and conductance modulation linearity, which directly decide the essential synaptic functions. [ 22–24 ]…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the V RESET sweep ranges of state 1 and state 2 are 0 to À2 V and 0 to À2.5 V, respectively, which are applied to the memristor. As previous reports [20,21] have demonstrated the good retention characteristics (generally longer than 10 3 s) of multilevel states in memristors based on multilayer oxide switching layers, our present work mainly focuses on the multilevel storage feature of our designed memristor, and only the stability of storage state 1 was measured as an example to confirmed its endurance. Figure 3b shows the typical dc retention data for both high-resistance state (HRS) and low-resistance state (LRS) up to 10 3 s at room temperature under a reading voltage of 0.2 V, indicating the good data retention of our memristor.…”
Section: Resultsmentioning
confidence: 88%
“…To describe the operating principle of the optimized device, schematic diagrams of the formation and rupture process of conductive filaments are proposed based on previous reports on memristors with multilayer oxides. [20,21] The initial state of the device is schemed in Figure 4a. It has been widely recognized that the TiO x and HfO x dielectric layers prepared by ALD are amorphous due to the presence of plentiful oxygen vacancies (V O ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The forming voltages of the IWZOx/IWZOy device range from 1.2 V to 2.1 V, which is more concentrated than IWZOx and IWZOy devices. In addition, when the device executed the first reset process, it was observed that the current of IWZOx/IWZOy device is smaller and more uniform than other devices [26,27]. During the process (1), a conductive filament is formed with the dissociated Cu ion between the Cu and Pt electrode.…”
Section: Resultsmentioning
confidence: 99%